(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The main objectives of the study were to find out the level of emotional intelligence of teacher educators and to find out the significant difference in emotional intelligence with regard to gender and location of Residence. The sample consists of 194 Teacher Educators working in various colleges of education in Tirunelveli district. Emotional Intelligence scale was used as tool to collect the data